Automatic fish feeders for fish farming in aquariumsbased on the Internet of Things (IOT) - Michael Angello Handoko Putra; Hadid Imron; Tommy Adhitya; Budi Wibowo (Jurnal Komputer dan Elektro Sains, 2023)
In fish farming, there is a lot of time in feeding irregularly or many farmers who have many fish aquariums but have difficulty in feeding because of the inefficiency of very little time and resulting in many fish causing stress and some fish that die. This research presents an innovation that changes the way to care for fish in an aquarium. Using Internet of Things (IoT) technology and Arduino Uno, this automatic fish feeding system was created with a focus on energy efficiency and fish welfare. With an internet connection, farmers can control and monitor the feeders through an app. The system also optimizes the use of electrical energy and monitors the environmental conditions of the aquarium in real time. This research offers a stunning innovation, combining technology and sustainability to better care for fish.